The effects of DDGS inclusion on pellet quality and pelleting performance - Fahrenholz, Adam C. (Kansas State University, 2008)
Three experiments were conducted to evaluate the effects of distillers dried grains with solubles (DDGS) on pellet quality and pellet mill performance in pelleted swine diets. The experiments were completed at the Feed Processing Research Center in the Department of Grain Science at Kansas State University. In all experiments, pellet durability index (PDI), electrical energy consumption, production rate, and bulk density served as the response criteria. In Exp. 1, DDGS were substituted on an equal weight basis for corn, with substitution levels of 10%, 20%, 30%, and 40%. The diet was not adjusted to maintain equal nutrient levels across the treatments. There were no observed significant differences in pellet quality across all levels of DDGS substitution. Both production rate and bulk density were significantly lowered as DDGS level increased. In Exp. 2, diets were formulated to contain the same levels of DDGS, but all ingredients were allowed to vary to retain nutritionally similar diets. In this case energy consumption showed no significant differences among treatments, while pellet quality, throughput, and bulk density were all negatively affected by increasing levels of DDGS. In Exp. 3, the effect of incorporating pelleted and reground DDGS was evaluated. The levels of DDGS evaluated were 10%, 20%, and 30%, using the same diets as Exp. 2. These diets were then pelleted and compared to a control diet with no added DDGS and to diets with unprocessed DDGS added at the same levels. At levels above 10% the diets containing unprocessed DDGS had significantly lower pellet quality than the control, while the diets containing pelleted and reground DDGS showed no significant difference from the control at any level. Significant effects were also observed for production rate, energy consumption, and bulk density. In conclusion, the use of standard DDGS in pelleted feeds is feasible, and although pellet quality may be significantly lower for feeds containing DDGS, the practical value is likely not affected. Furthermore, the data demonstrates some benefits of using DDGS that have been pelleted and reground.
Keywords: DDGS; pelleting; reground; pellet; quality; Agriculture, Animal Culture and Nutrition (0475)